Echocardiography in the preparticipation screening: an old topic revisited. Issue 5 (17th March 2023) - Donati, Federica; Guicciardi, Claudio; Lodi, Elisa; Fernando, Fredrick; Palermi, Stefano; Modena, Maria Grazia; Biffi, Alessandro
Abstract : Background: Preparticipation screenings have been conceived for the potential to prevent sudden cardiac death in young athletes by early identification of hidden cardiac diseases. Commonly used protocols include family history collection, physical examination, and resting electrocardiogram. Transthoracic echocardiography has been hypothesized to have a primary role in the preparticipation screening. Aims: The present study aimed to evaluate the additional role of echocardiogram in identifying cardiovascular abnormalities that might be undetected by commonly used preparticipation screening. Methods: We retrospectively reviewed Ferrari Formula Benessere, a corporate wellness program database, and analyzed data recorded from 2017 to 2022 to compare two medical models: a 'standard' preparticipation screening including medical history, physical examination, electrocardiogram and exercise stress testing versus an 'advanced' preparticipation screening comprising history, physical examination, electrocardiogram, exercise stress testing and echocardiography. Results: From an initial sample size of 7500 patients, we included 500 patients (420 male, 33.69 ± 7.9 mean age) enrolled for the first time in the corporate wellness program between 2017 and 2022. Three hundred and thirty-nine (67.8%) patients had no abnormal findings at 'standard' preparticipation screening and, even if they would have not required further evaluation, we performed echocardiography anyway ('advanced' preparticipation screening): 31 (9.1%) showed some abnormal cardiovascular findings at echocardiography, such as patent foramen ovalis, bicuspid aortic valve, aortic root ectasia or mitral valve prolapse. Conclusions: Screening echocardiogram showed an additional value (about 10% more) in detecting patients with cardiovascular abnormalities, otherwise undiagnosed with the 'standard' preparticipation screening protocol.